Computed tomographic-dacryocystography (CT-DCG) of the normal canine nasolacrimal drainage system with three-dimensional reconstruction - Rached, Paula A. [UNESP]; Canola, Julio C. [UNESP]; Schlueter, Claudia; Laus, Jose L. [UNESP]; Oechtering, Gerhard; de Almeida, Denise E. [UNESP]; Ludewig, Eberhard (Wiley-Blackwell, 2011)
The aims of the study were (1) to quantify the influence of selected imaging parameters on the image quality (slice thickness, mAs, and beam orientation) defining optimal conditions for scan protocols and (2) to evaluate the benefits of the 3D reconstruction techniques for visualization of NDS structures in dogs. CT-DCG was performed bilaterally in 32 heads of dogs. CT transverse images were obtained using a combination of two slice thickness values (0.8 mm and 2 mm) and two mAs values (50 mAs and 300 mAs). Two beam projection orientations were also tested: transverse plane (perpendicular to the hard palate) and oblique to the hard palate. Three-dimensional images were obtained using Volume Rendering (VR). Transverse beam projection proved to be superior for the assessment of the inferior and superior lacrimal canaliculi and lacrimal sac. In this study, there was no statistical difference regarding mAs values (50 mAs and 300 mAs) and slice thickness values (0.8 mm and 2 mm). Three-dimensional images were helpful for the assessment of topographic relationship between nasolacrimal structures and cranial landmarks.
Keywords: Canine; Computed tomography; CT-DCG; Dacryocystography; Dog; Nasolacrimal system